2009
DOI: 10.1007/s10661-009-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the fish farms on the water column nutrient concentrations and accumulation of heavy metals in the sediments in the eastern Aegean Sea (Turkey)

Abstract: We investigated potential effects of the fish farms on water column and sediment around Salih Island in the Gulluk Bay (Aegean Sea, Turkey) where four seasonal samplings were performed from October 2001 to August 2002. One measured physicochemical variables in water column including dissolved oxygen, nutrients (nitrite, nitrate, ammonium, phosphate and silicate), particulate organic carbon (POC) and chlorophyll a. Organic matter, total organic carbon (TOC) and heavy metals (Zn, Cu and Fe) were measured in sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 25 publications
5
31
0
1
Order By: Relevance
“…Cu, Zn and Cd seem to be the main metals released to the environment due to fish farm activities (Dean et al, 2007;Basaran et al, 2010). In the present work, according to PCA, Cu, Cd, Se, and, to some extent Zn, seem to have a similar accumulation dynamics as TOC, TON and TP along the distance gradient (Fig.…”
Section: Eliminado: Ysupporting
confidence: 63%
“…Cu, Zn and Cd seem to be the main metals released to the environment due to fish farm activities (Dean et al, 2007;Basaran et al, 2010). In the present work, according to PCA, Cu, Cd, Se, and, to some extent Zn, seem to have a similar accumulation dynamics as TOC, TON and TP along the distance gradient (Fig.…”
Section: Eliminado: Ysupporting
confidence: 63%
“…This is in agreement with the hypothesis that the sedimentation of uneaten feed and faeces could be a source of Zn, whereas most of the Cu concentration originates from a different source (i.e. antifouling paints), which varies widely according to the frequency of net maintenance with antifouling paints and the hydro dynamics at each farm (Uotila 1991, Chou et al 2002, Belias et al 2003, Dean et al 2007, Basaran et al 2010, Wu & Yang 2010, Kalantzi et al 2013b. Several previous studies have reported elevated concentrations of elements such as Cu and Zn, which are associated with anti-fouling use, in marine surface sediments (De bourg et al 1993, Burridge et al 1999, Børufsen Solberg et al 2002, Chou et al 2002, Parker & Aube 2002, Brooks & Mahnken 2003.…”
Section: Discussionsupporting
confidence: 83%
“…A meta-analysis of 30 peer-reviewed articles (Sarà 2007) concluded that dissolved oxygen was generally not affected by aquaculture operations. In the Aegean Sea, tuna and sea bass farms were monitored (Basaran et al 2007, Yabanh & Egemen 2009, Aksu et al 2010, with no effects detected. VargasMachuca et al (2008) found no impacts on dissolved oxygen at snapper farms off Mexico's Pacific coast.…”
Section: Studies Reporting No Significant Decreasementioning
confidence: 99%